Simulation and Analysis of a Turbulent Flow Around a Three-Dimensional Obstacle - Benahmed Lamia (Acta Mechanica et Automatica, 2019)
The study of flow around obstacles is devised into three different positions: above the obstacle, upstream of the obstacle, and downstream of the latter. The behaviour of the fluid downstream of the obstacle is less known, and the physical and numerical modelling is being given the existence of recirculation zones with their complex behaviour. The purpose of the work presented below is to study the influence of the inclined form of the two upper peaks of a rectangular cube. A three-dimensional study was carried out using the ANSYS CFX calculation code. Turbulence models have been used to study the flow characteristics around the inclined obstacle. The time-averaged results of contours of velocity vectors <V>, cross-stream <v> and stream wise velocity and streamlines were obtained by using K-ω shear -stress transport (SST), RANG K-ε and K-ε to model the turbulence, and the governing equations were solved using the finite volume method. The turbulence model K-ω SST has presented the best prediction of the flow characteristics for the obstacle among the investigated turbulence models in this work.